2016
DOI: 10.1136/bcr-2016-214737
|View full text |Cite
|
Sign up to set email alerts
|

Phaeochromocytoma presenting as an acute coronary syndrome

Abstract: A 44-year-old Caucasian man presented to the emergency department in acute cardiogenic shock, with pulmonary oedema, secondary to an acute myocardial infarction and in a hyperosmolar hyperglycaemic state. The previous day he had undergone a colonoscopy, which revealed features of colitis, and was started on prednisolone. He had been previously diagnosed with type 2 diabetes, migraine and anxiety attacks. While awaiting a coronary angiogram he developed abdominal pain and a CT scan was performed and found a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The coronary angiogram showed nonobstructed coronary arteries. We noted that most of such patients had few significant coronary atherosclerosis in past reports[ 8 - 10 ]. Most reports suggested that cardiomyopathy, severe coronary vasospasm, myocarditis, and tachycardia caused by excessive release of catecholamines result in elevated cardiac troponin and reduced left ventricular systolic function[ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 72%
“…The coronary angiogram showed nonobstructed coronary arteries. We noted that most of such patients had few significant coronary atherosclerosis in past reports[ 8 - 10 ]. Most reports suggested that cardiomyopathy, severe coronary vasospasm, myocarditis, and tachycardia caused by excessive release of catecholamines result in elevated cardiac troponin and reduced left ventricular systolic function[ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 72%
“…These tumours release rapid and massive amount of catecholamines that can cause life-threatening cardioand cerebrovascular complications (3). Data in 2012 showed 19.3% subjects with pheochromocytoma had a relatively high incidence of cardiovascular complications.…”
Section: Introductionmentioning
confidence: 99%